A review and roadmap of the skin, lung and gut microbiota in systemic sclerosis. (18th March 2021) - Teaw, Shannon; Hinchcliff, Monique; Cheng, Michelle
Abstract: As our understanding of the genetic underpinnings of SSc increases, questions regarding the environmental trigger(s) that induce and propagate SSc in the genetically predisposed individual emerge. The interplay between the environment, the immune system, and the microbial species that inhabit the patient's skin and gastrointestinal tract is a pathobiological frontier that is largely unexplored in SSc. The purpose of this review is to provide an overview of the methodologies, experimental study results and future roadmap for elucidating the relationship between the SSc host and his/her microbiome.